Mechanisms of Immunosuppressive Tumor Evasion: Focus on Acute Lymphoblastic Leukemia - Jiménez-Morales, Silvia; Aranda-Uribe, Ivan Sammir; Pérez-Amado, Carlos Jhovani; Ramírez-Bello, Julian; Hidalgo-Miranda, Alfredo (Frontiers in Immunology, 2021)
Acute lymphoblastic leukemia (ALL) is a malignancy with high heterogeneity in its biological features and treatments. Although the overall survival (OS) of patients with ALL has recently improved considerably, owing to the application of conventional chemotherapeutic agents, approximately 20% of the pediatric cases and 40–50% of the adult patients relapse during and after the treatment period. The potential mechanisms that cause relapse involve clonal evolution, innate and acquired chemoresistance, and the ability of ALL cells to escape the immunesuppressive tumor response. Currently, immunotherapy in combination with conventional treatment is used to enhance the immune response against tumor cells, thereby significantly improving the OS in patient with ALL. Therefore, understanding the mechanisms of immune evasion by leukemia cells could be useful for developing novel therapeutic strategies.